2003
DOI: 10.1046/j.1365-2044.2003.03201.x
|View full text |Cite
|
Sign up to set email alerts
|

New aspects of ventilation in acute lung injury

Abstract: Summary Recent recognition that artificial ventilation may cause damage to the acutely injured lung has caused renewed interest in ventilation techniques that minimise this potential harm. Many ventilation techniques have proved beneficial in small trials of very specific patient groups, but most have subsequently failed to translate into improved patient outcome in larger trials. An exception to this is ‘protective ventilation’ using reduced tidal volumes (to lower airway pressure) and increased PEEP (to redu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 166 publications
(200 reference statements)
0
10
0
Order By: Relevance
“…6 In patients with injured lungs, this often leads to high peak inflation and plateau pressures, with risk of over-distension of the lungs and a significant risk of volutrauma and barotrauma. 7 Moreover, a significant amount of experimental data in animals suggests that over-distension of the alveoli perpetuates lung injury with induction of cytokine release, leading to further lung injury or biotrauma 8,9 and dysfunction of other distant organs. As a result, an approach of "protective ventilation" has been developed.…”
Section: Ventilatory Management Of Patients With Pgdmentioning
confidence: 99%
See 1 more Smart Citation
“…6 In patients with injured lungs, this often leads to high peak inflation and plateau pressures, with risk of over-distension of the lungs and a significant risk of volutrauma and barotrauma. 7 Moreover, a significant amount of experimental data in animals suggests that over-distension of the alveoli perpetuates lung injury with induction of cytokine release, leading to further lung injury or biotrauma 8,9 and dysfunction of other distant organs. As a result, an approach of "protective ventilation" has been developed.…”
Section: Ventilatory Management Of Patients With Pgdmentioning
confidence: 99%
“…7 With specific reference to pulmonary PGD, the only study to date examining ventilation-induced lung injury in lung transplantation was an animal study performed by the University of Toronto group. 14 In a rat lung transplant model, traditional ventilation was compared with a "minimal mechanical stress" mode (significantly lower tidal volumes, with adjusted higher PEEP).…”
Section: Ventilatory Management Of Patients With Pgdmentioning
confidence: 99%
“…Both experimental and clinical studies have suggested that mechanical ventilation using large tidal volumes could initiate lung injury in healthy lungs, a phenomenon referred as ventilator induced lung injury [1][2][3][4][5][6][7][8][9]. Previous animal [10] and human [11][12][13][14] studies have reported that large tidal volumes and high airway pressures impact adversely on pulmonary and systemic inflammatory responses of non-healthy lungs [15]. Large epidemiological studies of ventilatory practices in patients in the intensive care unit (ICU) have been performed both in Europe and in the USA [16][17][18].…”
mentioning
confidence: 99%
“…A cyclic change in pulmonary volume may be a significant cause of MVIPI, suggesting that a ventilation strategy avoiding major pulmonary volume variations might be beneficial. (7,8) The concept of protective mechanical ventilation emerged from the understanding of VILI. It may be defined as a ventilation that minimizes tidal volume, maintains a low peak inspiratory pressure, offers a sufficient positive end expiratory pressure (PEEP) to maintain alveolar opening, avoiding alveolar collapse and cyclic opening and closing of the alveolar units, uses non-toxic concentrations of oxygen and permits hypercapnia.…”
Section: Introductionmentioning
confidence: 99%
“…In such cases, when protective mechanical ventilation is mandatory, high frequency oscillatory ventilation (HFOV) becomes an attractive alternative. (9) HFOV is a ventilation mode that uses a lower tidal volume than the anatomic dead space volume (1-3 mL/Kg) with a frequency well above the physiological one (5)(6)(7)(8)(9)(10), that is to say, 300-600 cycles/ minute). This ventilation mode has been successfully used to treat patients with severe respiratory failure when CMV fails, Furthermore, reports state that when HFOV is used earlier, together with a protective strategy, a decrease of the acute or chronic pulmonary injury occurs in patients with ARDS.…”
Section: Introductionmentioning
confidence: 99%